Cluster Analysis for Extension and Other Behavior Change Practitioners: Information and Terminology Needed for Cluster Analysis - Laura A. Warner (EDIS)
By identifying audience subgroups, cluster analysis (a quantitative technique) helps Extension agents tailor their education and communication programs to specific audiences. This publication falls under the Cluster Analysis for Extension and Other Behavior Change Practitioners series and discusses key information and terminology associated with cluster analysis. The publication thus builds upon “Cluster Analysis for Extension and Other Behavior Change Practitioners: Introduction,” which introduced cluster analysis as a technique for audience segmentation. This publication provides essential information for the publications which follow, “A Practical Example” and “Integrating the Results of Cluster Analysis into Meaningful Audience Engagement.”